2021
DOI: 10.1212/cpj.0000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic Seizure Detection by Neuroscience Intensive Care Unit Nurses via Bedside Real-Time Quantitative EEG

Abstract: Objective:Our primary objective was to determine the performance of real-time Neuroscience ICU (Neuro ICU) nurse interpretation of quantitative EEG (qEEG) at the bedside for seizure detection. Secondary objectives included determining nurse time to seizure detection and assessing factors that influenced nurse accuracy.Methods:Nurses caring for Neuro ICU patients undergoing cEEG were trained using a 1-hour qEEG panel (rhythmicity spectrogram and amplitude-integrated EEG) bedside display. Nurses’ hourly interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Besides, several studies have suggested that non-EEG experts such as bedside ICU personnel can be trained in the acquisition and troubleshooting of EEGs, as well as screening uninterrupted raw EEG for seizure detection purposes [ 22 , 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Besides, several studies have suggested that non-EEG experts such as bedside ICU personnel can be trained in the acquisition and troubleshooting of EEGs, as well as screening uninterrupted raw EEG for seizure detection purposes [ 22 , 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Trends may include spectral power (amplitude of individual frequency bands summed over time), power ratios, variability, rhythmicity, asymmetry, and some tools for spike detection. With training, critical care nurses and other non-neurophysiologists can accurately assess panels displaying real-time qEEG measures such as spectral power, typically reviewing short segments of 15–60 min at a time to identify periods of high-suspicion EEG activity [ 36 , 202 , 203 ]. Following brief qEEG interpretation training 65 ICU nurses achieved 74% sensitivity and 92% specificity in identifying seizures, detecting these seizures 132 min faster than standard neurophysiology practices, although detecting brief events may necessitate zooming in on shorter EEG epochs [ 203 ].…”
Section: Practical Considerations and Implementation In Critical Carementioning
confidence: 99%
“…With training, critical care nurses and other non-neurophysiologists can accurately assess panels displaying real-time qEEG measures such as spectral power, typically reviewing short segments of 15–60 min at a time to identify periods of high-suspicion EEG activity [ 36 , 202 , 203 ]. Following brief qEEG interpretation training 65 ICU nurses achieved 74% sensitivity and 92% specificity in identifying seizures, detecting these seizures 132 min faster than standard neurophysiology practices, although detecting brief events may necessitate zooming in on shorter EEG epochs [ 203 ]. Integrating qEEG interpretation training with user-friendly tools empowers non-experts, including critical care nurses, to monitor EEG data for potential seizure activity effectively, promising faster and more accurate seizure detection and improved intervention timing and quality.…”
Section: Practical Considerations and Implementation In Critical Carementioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Neurology ® Clinical Practice , Kaleem et al 6 report on a prospective single-center study that evaluated the performance of neuro-ICU nurses for seizure detection by real-time bedside qEEG interpretation. In addition, the authors evaluated time to seizure detection and factors associated with interpretation inaccuracy.…”
mentioning
confidence: 99%